STUDI TENTANG PENGGUNAAN ALAT EVALUASI PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 1 BABAT LAMONGAN - NOVI WULANSARI (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
In the Ministerial Regulation No. Nasioanal Education. 41 of 2007 on the assessment of learning outcomes explained that in order to make an assessment or evaluation, should be done consistently, sisitematik, and programmed using tests and nontes in the form of written or verbal, performance observation, measurement of attitudes, valuation the work in the form of assignments, projects and or products, portfolios, and self-assessment. This suggests that assessment in a school not only academic skills are assessed but also should pay attention to personal skills and social skills. This descriptive type of research. Sources of data obtained from primary and secondary sources. Data collection instruments used in this research is the study of sheet questionnaire to experts. The technique used to obtain the necessary data in this study are interviews and documentation. Feasibility Peresentase obtained by calculations based on Guttman scale. The results of the interview stated that the evaluation is done through a written test only. Of the four questions on a matter that is KD 4, 5, 6, and 7, can be categorized that questions used accounting teacher at SMAN 1 Lamongan tripe deserves to students. Keyword: Evaluation Instrument, Feasibility, Accounting